The Everyday Implications of Ethnic-Racial Identity Processes: Exploring Variability in Ethnic-Racial Identity Salience Across Situations - Douglass, Sara (J Youth Adolesc, 2015)
Given the social and developmental relevance of ethnicity-race during adolescence, it is important to understand the meaning of ethnic-racial identity in adolescents’ everyday lives. The current study considered how individual differences in ethnic-racial identity exploration (i.e., the extent to which individuals have explored their ethnicity-race), and commitment (i.e., the extent which they have a clear sense of what it means to them) influenced variability versus stability in the awareness of ethnicity-race in a given situation (i.e., salience), and how this variability is related to mood in that situation. Within an ethnic/racially diverse sample of 395 adolescents (M(age) = 15; 63 % female; 12 % Black, 26 % Latino, 34 % Asian, 23 % White), results indicated that ethnic-racial identity exploration was unrelated to variability in salience, while commitment promoted stability in salience across situations. Further, among adolescents who were generally very aware of their ethnicity-race, increases in situational salience were related to decreased negative and anxious mood. Among adolescents who were generally not aware of their ethnicity-race, increases in situational salience were related to increased positive and decreased negative mood. Implications for understanding the developmental and everyday experiences of ethnic-racial identity are discussed.